2019
DOI: 10.1590/s1678-9946201961009
|View full text |Cite
|
Sign up to set email alerts
|

Entomological and virological surveillance for dengue virus in churches in Merida, Mexico

Abstract: This study was designed to assess whether churches in endemic dengue districts in Merida, Mexico provide suitable breeding habitats for mosquitoes and are potential sites for dengue virus (DENV) transmission. Churches were inspected for immature and adult mosquitoes once every week from November 2015 to October 2016. A total of 10,997 immatures of five species were collected. The most abundant species were Aedes aegypti (6,051) and Culex quinquefasciatus (3,018). The most common source of immature Ae. aegypti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(59 reference statements)
1
2
0
1
Order By: Relevance
“…The infectivity rates are lower when virological surveillance is independent from the reporting of positive cases, as is the case in the present study. This is corroborated by Baak-Baak et al 23 , who found 1.2% (2/166) positivity for dengue virus in churches. Meanwhile, in Belo Horizonte, the State capital of Minas Gerais, Eiras et al 24 found 4.9% (4/82 pools) and 8.5% (7/82 pools) infectivity to dengue virus and Zika virus, respectively, at the university Moreover, the possibility of transovarian transmission of dengue 25 , chikungunya 26 and Zika 27,28 in Ae.…”
Section: Discussionsupporting
confidence: 68%
“…The infectivity rates are lower when virological surveillance is independent from the reporting of positive cases, as is the case in the present study. This is corroborated by Baak-Baak et al 23 , who found 1.2% (2/166) positivity for dengue virus in churches. Meanwhile, in Belo Horizonte, the State capital of Minas Gerais, Eiras et al 24 found 4.9% (4/82 pools) and 8.5% (7/82 pools) infectivity to dengue virus and Zika virus, respectively, at the university Moreover, the possibility of transovarian transmission of dengue 25 , chikungunya 26 and Zika 27,28 in Ae.…”
Section: Discussionsupporting
confidence: 68%
“…La incidencia de esta infección ha aumentado a gran escala durante estas dos décadas, y se convirtió en endémica en varias regiones del mundo, aquellas personas que sufrieron una infección previa desarrollaron permeabilidad capilar severa y sangrado después de infectarse con otra especie, a esto se le denomina como dengue hemorrágico (9). La Organización Mundial de la Salud ha divido los casos de dengue en dos categorías clínicas: grave y no grave, la forma grave es similar a una infección viral indiferenciada, un caso probable se describe con fiebre, náuseas y vómitos, sarpullido, leucopenia, entre otros, y se necesitaría de pruebas de laboratorio para su confirmación (10).…”
Section: Dengueunclassified
“…and entomological data should be collected in dengue infection surveillance [7], [8], [9], [10] by conducting home visits to record larva density per region and case. Environmental factors also affect the density of larvae and mosquitoes such as the number of potential breeding places [11], [12], [13], [14].…”
Section: Epidemiologicalmentioning
confidence: 99%